Anti-inflammatory Effect of Curcumin, Homotaurine, and Vitamin D3 on Human Vitreous in Patients With Diabetic Retinopathy - Filippelli, Mariaelena; Campagna, Giuseppe; Vito, Pasquale; Zotti, Tiziana; Ventre, Luca; Rinaldi, Michele; Bartollino, Silvia; dell'Omo, Roberto; Costagliola, Ciro (Frontiers in Neurology, 2021)
Purpose: To determine the levels of pro-inflammatory cytokines and soluble mediators (TNF-α, IL6, IL2, and PDGF-AB) in 28 vitreous biopsies taken from patients with proliferative diabetic retinopathy (PDR) and treated with increasing doses of curcumin (0. 5 and 1 μM), with or without homotaurine (100 μM) and vitamin D3 (50 nM). Materials and Methods: ELISA tests were performed on the supernatants from 28 vitreous biopsies that were incubated with bioactive molecules at 37°C for 20 h. The concentration of the soluble mediators was calculated from a calibration curve and expressed in pg/mL. Shapiro-Wilk test was used to verify the normality of distribution of the residuals. Continuous variables among groups were compared using the General Linear Model (GLM). Homoscedasticity was verified using Levene and Brown-Forsythe tests. Post-hoc analysis was also performed with the Tukey test. A p ≤ 0.05 was considered statistically significant. Results: The post-hoc analysis revealed statistically detectable changes in the concentrations of TNF-α, IL2, and PDGF-AB in response to the treatment with curcumin, homotaurine, and vitamin D3. Specifically, the p-values for between group comparisons are as follows: TNF-α: (untreated vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.008, (curcumin 0.5 μM vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.0004, (curcumin 0.5 μM vs. curcumin 1 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.02, (curcumin 1 μM vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.025, and (homotaurine 100 μM + vitamin D3 50 nM vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.009; IL2: (untreated vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.0023, and (curcumin 0.5 μM vs. curcumin 0.5 μM+ homotaurine 100 μM + vitamin D3 50 nM) p = 0.0028; PDGF-AB: (untreated vs. curcumin 0.5 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.04, (untreated vs. curcumin 1 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.0006, (curcumin 0.5 μM vs. curcumin 1 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.006, and (homotaurine 100 μM + vitamin D3 50 nM vs. curcumin 1 μM + homotaurine 100 μM + vitamin D3 50 nM) p = 0.022. IL6 levels were not significantly affected by any treatment. Conclusions: Pro-inflammatory cytokines are associated with inflammation and angiogenesis, although there is a discrete variability in the doses of the mediators investigated among the different vitreous samples. Curcumin, homotaurine, and vitamin D3 individually have a slightly appreciable anti-inflammatory effect. However, when used in combination, these substances are able to modify the average levels of the soluble mediators of inflammation and retinal damage. Multi-target treatment may provide a therapeutic strategy for diabetic retinopathy in the future. Clinical Trial Registration : The trial was registered at clinical trials.gov as NCT04378972 on 06 May 2020 (“retrospectively registered”) https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid = S0009UI8&selectaction = Edit&uid = U0003RKC&ts = 2&cx = dstm4o.